Pengaruh Pembelajaran Daring Terhadap Hasil Belajar Siswa pada Tema Benda-benda Sekitar Kita di Kelas V SDN 107400 Bandar Khalifah - Mastari Ramadhani (Multiverse: Open Multidisciplinary Journal, 2022)
The Effect of Online Learning on Student Learning Outcomes on the Theme of Objects Around Us in Class V SDN 101752 Klambir Five Academic Years 2020/2021. Thesis. Primary School Teacher Education Department. Faculty of Science Education. Nahdlatul Ulama University, North Sumatra. This study aims to determine the effect of online learning on student learning outcomes on the theme of objects around us in fifth grade elementary school. The subjects of this study were the fifth grade students of SDN 101752 Klambir Lima, totaling 36 people, consisting of 19 boys and 17 girls. This study uses descriptive quantitative research with data testing using SPSS 25. Data obtained through filling out questionnaires by respondents, data from schools and interviews as supporting data. This study tested the validity, reliability, normality and hypothesis testing. The results showed that online learning had a significant effect on student learning outcomes. It is proven from the results of testing the validity of the value of sig.(2-tailed) is <0.05. Judging from rcount and rtable, the result is that the value of rcount > rtable. The rtable value of 0.2785 was obtained from looking at the respondent's data. The results of the reliability test are known that the value of Cronbach's alpha > 0.6. The results of the Kolmogorov Smirnov normality test with SPSS are known that the value of Sig = 0.200> 0.05, so it can be concluded that the residual value is normally distributed. The value of the coefficient of determination is 67,1% and the remaining 32.9% is explained by other variables not explained in this study. And the results of the hypothesis test show that the value of fcount and ftable = 69,234 > 4.121. From the test results, it can be concluded that online learning can be a substitute for face-to-face learning during the COVID-19 pandemic. Keywords: Online Learning, Student Learning Outcomes.